The Production of AZ31 Alloys by Gas Atomization Method and Its Characteristics - Em Akra, K. M.; Akkas, M.; Boz, M.; Seabra, Eurico (Allerton Press, 2020)
The aim of this study is to investigate the AZ31 alloy powder production and characterization processes experimentally using the gas atomization method. For this purpose, firstly, the design and production of gas atomization units were done at Karabuk University Faculty of Technology Department of Manufacturing Engineering. In this gas atomization unit, the manufacturability of AZ31 powder from magnesium alloys was investigated by the gas atomization method which is one of the production methods by powder metallurgy. The parameters and the literature used in the production of materials similar to the AZ31 alloy are taken into account as producibility parameters. In the gas atomization method, parameters such as nozzle diameter, gas pressure, and temperature must be controlled in order to produce the desired properties in metal powder production. The diameter of the nozzle is crucial because it affects the gas pressure and temperature, the size of the powder, and the shape of the powders. Experimental studies were carried out using 3 different temperatures (790, 820, and 850°C), 4 different nozzle diameters (2, 3, 4, and 5 mm) and 4 different gas pressures (5, 15, 25, and 35 bar). In the molten metal atomization process and in the process of forming a protective gas atmosphere, argon gas was preferred. Scanning electron microscopy (SEM) was used to determine the shape of the AZ31 powders produced, XRD, XRF, and SEM-EDX analyses were used to determine the phases in the internals of the produced powders and percentages of these phases. Laser measurement devices were used for powder size analysis and hardness tests were performed to determine the mechanical properties of the produced powders. The powders produced were pressed into masses at 4 different pressing pressures (300, 400, 500, and 600 MPa). The best sinterability values of the bulked powders and sintering process were performed at 3 different temperatures (500, 550, and 600°C). Density measurements were made after pressing and sintering the powders. As a result of the experimental studies, it was found that the powder size decreased with the increase of the gas pressure but the nozzle diameter, and the powder shape changed to the dripping and the spherical in the ligament and complex form. It has been observed that the temperature has no significant effect on the powder size and shape.
Keywords: powder metallurgy; gas atomization; powder production; AZ31 alloy; magnesium